The Cave 3 Copper Scroll a symbolic journey - Høgenhaven, Jesper 1961- (Leiden Boston Brill, 2020)
"In The Cave 3 Copper Scroll: A Symbolic Journey, Jesper Høgenhavn presents a reading of the Copper Scroll as a literary text. For more than 60 years, scholars have debated whether or not the treasures recorded here reflect historical realities. This study argues that the dichotomy between "facts" and "fiction" is inadequate for a proper understanding of the Copper Scroll. The document was designed to convey specific images to its readers, thus staying true to the format of an instruction for retrieving hidden treasures. Yet, the evoked landscape is dense with symbolical associations, and the journey through it reflects deliberate narrative patterns. The scroll was written against the background of the social and political turmoil of Jewish Palestine in the 1st century CE, and reflects contemporary concerns and interests"--
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Copper Scroll